Adjustable compliance soft gripper system. (2nd August 2019) - Sârbu, F; Deaconescu, A; Deaconescu, T
This article proposes a novel, innovative, soft gripper system developed for the manipulation of objects of unknown or unspecified shape and consistence. This could be achieved by the utilization of a linear pneumatic muscle benefitting from an inherently compliant behaviour. A gripper system of this type does not require the presence of sensors or complex controllers, as it is the mechanical system itself that provides the required adaptive behaviour. The compliance of the system is ensured by the variations of the air pressure fed to the pneumatic muscle, monitored and controlled in a closed loop by means of proportional pressure regulator.